Strategi Islamic Estate Planning dalam Pembagian Harta Warisan Berdasarkan Hukum Faraidh - Muhammad Firmansyah; Priyonggo Suseno (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Inheritance planning in Islam is part of wealth management, encompassing both material and spiritual aspects. The distribution of assets is carried out fairly in accordance with Islamic law through the faraidh system to maintain harmony and blessings. In addition to faraidh, planning can also involve gifts, Islamic insurance, and waqf to prevent conflict and ensure that assets benefit the family and community.The goal of Islamic inheritance planning is to ensure the distribution of assets in accordance with Islamic estate planning principles and the laws of faraidh, to create justice, prevent disputes, and emphasize inheritance as an act of worship and a moral responsibility. Furthermore, the use of gifts, waqf, and Islamic insurance aims to ensure that assets continue to provide benefits and blessings on an ongoing basis. Inheritance planning has been implemented in accordance with the principles of faraidh and Islamic provisions, with a properly calculated heir structure. This demonstrates the alignment between planning practices and Islamic law. However, formal legal aspects need to be strengthened by creating a will that is valid according to Islamic law and state law. Therefore, it is recommended to involve an attorney or notary to ensure the distribution of assets is fair, valid, and free from disputes